Field‐Aligned Isotropic Surface Remeshing. (28th February 2018) - Du, Xingyi; Liu, Xiaohan; Yan, Dong‐Ming; Jiang, Caigui; Ye, Juntao; Zhang, Hui
Abstract: We present a novel isotropic surface remeshing algorithm that automatically aligns the mesh edges with an underlying directional field. The alignment is achieved by minimizing an energy function that combines both centroidal Voronoi tessellation (CVT) and the penalty enforced by a six‐way rotational symmetry field. The CVT term ensures uniform distribution of the vertices and high remeshing quality, and the field constraint enforces the directional alignment of the edges. Experimental results show that the proposed approach has the advantages of isotropic and field‐aligned remeshing. Our algorithm is superior to the representative state‐of‐the‐art approaches in various aspects. Abstract : We present a novel isotropic surface remeshing algorithm that automatically aligns the mesh edges with an underlying directional field. The alignment is achieved by minimizing an energy function that combines both centroidal Voronoi tessellation (CVT) and the penalty enforced by a six‐way rotational symmetry field. The CVT term ensures uniform distribution of the vertices and high remeshing quality, and the field constraint enforces the directional alignment of the edges. Experimental results show that the proposed approach has the advantages of isotropic and field‐aligned remeshing. Our algorithm is superior to the representative state‐of‐the‐art approaches in various aspects.